PENGEMBANGAN BAHAN AJAR BIOLOGI SMA PADA MATERI SISTEM INDRA MANUSIA MENGGUNAKAN MODEL PREDICT OBSERVE EXPLANT (POE) UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Ramadhan Batubara, Yude; Huda, M. Komarul; Saragih, Marlindoaman (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2023)
This study aims to determine the development of high school biology teaching materials and improve student learning outcomes using the Predict, Observe, and Explant (POE) learning model. The population in this study was 192 students, consisting of four classes, and the sample taken was one class from Kartika I-4 Private High School, Pematangsiantar. The sampling technique used was cluster random sampling, with a sample of 48 students. The instruments used to observe the development of high school biology teaching materials were assessment sheets filled out by observers for student assessment and expert validation in the subject of the human sensory system. The instruments used to assess the level of improvement in student learning outcomes were a pretest and posttest in the form of 20 multiple-choice questions, divided into two sessions, each with 10 questions. Data analysis was performed by calculating the average pretest and posttest scores for each session and calculating the observation scores for student assessment and expert validation. The results of this study obtained student learning outcomes and teaching materials that can be implemented at Kartika I-4 Private High School, Pematangsiantar.